Pupuk Hayati Cendawan Mikoriza Arbuskula (CMA) Gigaspora sp. pada Pembibitan Cabai Rawit (Capsicum frutescens L.) - Ngadiani Ngadiani; Vivin Andriani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Cayenne Pepper (Capsicum frutescens L.) is one of the horticultural crops that has the potential to be developed because of its high demand and role for consumption on a national scale and for export. Increasing the success of cultivation can be done by adding arbuscular mycorrhizal fungi (CMA). One of the CMA is Gigaspora sp. can be developed as a biological fertilizer agent because this fungus is a symbiotic mutualism. This study aims to determine the effect of the dose of CMA Gigaspora sp. against cayenne pepper plant nurseries. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments included G0 (Gigaspora spores only), G1 (Gigaspora spores + 15 grams of propagule), G2 (Gigaspora spores + 30 grams of propagule), G3 (Gigaspora spores + 45 grams of propagule) and control (K). The observed variables were growth including plant height, number of leaves, total dry weight, and percentage of colonization of Gigaspora sp. on the root. The results showed that there was an interaction between CMA Gigaspora sp. in single form or with a mixture of propagules can increase the growth of cayenne pepper plants. The administration of a mixture of propagules was more effective than the administration of Gigaspora sp. as a single spore after 75 days. Optimal treatment for 4 parameters, namely G3 (Gigaspora spores + 45 grams of propagule) which showed a plant height of 89.24 cm, number of leaves 60.14 strands, total dry weight 10.27 grams, and the percentage of colonization of Gigasporasp on roots of 84, 62%.